2019
DOI: 10.1038/s41598-019-51868-5
|View full text |Cite|
|
Sign up to set email alerts
|

Modeling Snyder-Robinson Syndrome in multipotent stromal cells reveals impaired mitochondrial function as a potential cause for deficient osteogenesis

Abstract: Patients with Snyder-Robinson Syndrome (SRS) exhibit deficient Spermine Synthase (SMS) gene expression, which causes neurodevelopmental defects and osteoporosis, often leading to extremely fragile bones. To determine the underlying mechanism for impaired bone formation, we modelled the disease by silencing SMS in human bone marrow - derived multipotent stromal cells (MSCs) derived from healthy donors. We found that silencing SMS in MSCs led to reduced cell proliferation and deficient bone formation in vitro, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 20 publications
(31 reference statements)
7
15
0
Order By: Relevance
“…Further experiments revealed that the prodrug unresponsive cells imported the prodrug but failed to effectively convert it to spermine suggesting a lower cellular reduction potential in specific SRS cell types. This is consistent with the known mitochondrial defects noted in SRS cells with specific mutations. , Further experiments showed that one could convert the recalcitrant fibroblast line to a prodrug-responsive line via preincubation with N -acetylcysteine (NAC).…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Further experiments revealed that the prodrug unresponsive cells imported the prodrug but failed to effectively convert it to spermine suggesting a lower cellular reduction potential in specific SRS cell types. This is consistent with the known mitochondrial defects noted in SRS cells with specific mutations. , Further experiments showed that one could convert the recalcitrant fibroblast line to a prodrug-responsive line via preincubation with N -acetylcysteine (NAC).…”
Section: Introductionsupporting
confidence: 78%
“…Previous studies have demonstrated that the SMS deficiency impairs mitochondrial function. , The dysfunction of mitochondria is linked to the oxidative state of the cell because mitochondria can be damaged by reactive oxygen species (ROS). Because the ROS hydrogen peroxide is a byproduct of spermidine catabolism, we speculated that the oxidative stress generated from the metabolism of the imbalanced polyamine pools in SRS cells may affect mitochondrial function and lower cellular reduction potential. , In short, ROS load could explain why certain SRS cells were recalcitrant to the prodrug.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better define the osteoporosis of SRS, Albert et al [2015] performed detailed studies on affected individuals and provided the first evidence supporting that SRS patients lose osteoblast and osteoclast activity and that the low bone density ocurring in SRS most likely arises by an intrinsic cellular process [Albert et al, 2015]. Furthermore, Ramsay et al [2019] modeled the disease by silencing SMS in multipotent stromal cells in human bone marrow and found what led to reduced cell proliferation and deficient bone formation in vitro, as evidenced by reduced mineralization and decreased bone sialoprotein expression. This study suggests that SMS deficiency causes strong transcriptomic and metabolic changes in multipotent stromal cells, which are possibly associated with the observed impaired osteogenesis both in vitro and in vivo [Ramsay et al, 2019].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ramsay et al [2019] modeled the disease by silencing SMS in multipotent stromal cells in human bone marrow and found what led to reduced cell proliferation and deficient bone formation in vitro, as evidenced by reduced mineralization and decreased bone sialoprotein expression. This study suggests that SMS deficiency causes strong transcriptomic and metabolic changes in multipotent stromal cells, which are possibly associated with the observed impaired osteogenesis both in vitro and in vivo [Ramsay et al, 2019].…”
Section: Discussionmentioning
confidence: 99%